The Global Trend of Leadership in Cluster Research: A Systematic Review Approach (Open Society Conference, 2023)
Leadership is a movement to influence how other people behave with the aim that they will be coordinated to achieve certain goals. Leadership is concerned with members who have distinctive features of a group that can be positively distinguished from other members in behavior, personal characteristics, thinking, or group structure. Meanwhile, management is a series of activities consisting of planning, implementation, supervision, and control to achieve certain goals that have been targeted through the use of human resources and other sources. This study uses a data analysis method, namely Systematic Analysis. This study uses the Systematic Literature Review (SLR) method to identify, analyze and discuss all the data needed in this study. Where the Systematic review method is known as a method that combines many original studies by classifying based on criteria. This method of search assesses and compiles all relevant empirical evidence to provide a complete interpretation of the research results. This research was built consisting of four major stages. The details of the major stages are explained separately. The stages and details of the stages will be followed by the implementation method. In the literature search process, the selection of search results is done by filtering the search results based on predetermined criteria. The criteria used are inclusion and exclusion which are then used as the basis for selecting literature. It was concluded that every leader in the organization must-have criteria that have been set by the company to be able to manage existing resources within the company, so the company will be able to more easily achieve the organizational goals that have been determined.